Citrobacter spp. bloodstream infection primarily affects the elderly either hospitalized or closely associated with health care – a population-based observational study with comparisons between C. koseri and the C. freundii complex - Sunnerhagen, Torgny ; 0000-0002-9240-2378; Taie, Hiba; Ohlsson, Johan; Ljungquist, Oskar (BMC Infectious Diseases, 2025)
Objectives Despite regularly being found in blood cultures, there are few studies of bloodstream infection (BSI) with Citrobacter. In this population-based study, the aim was to explore patient characteristics, outcome, and incidence in a publicly funded single payer setting. Methods Patients with growth of Citrobacter in blood culture were identified through the clinical microbiology laboratory in Lund, Sweden, for the year 2013–2023. This laboratory serves the whole Skåne region, with a population of 1.4 million. Medical records were retrospectively reviewed. Results 554 episodes of Citrobacter BSI were identified, with septic shock seen in 25 (4%) episodes and with 38 (7%) episodes resulting in intensive care. The 90-day mortality was 18% and the median age of the patients was 77 years. Resistance to cephalosporins was below 10%, and carbapenem resistance was not found in any isolates. A majority of episodes were healthcare associated or nosocomial, and almost half of BSI cases originated from the urinary tract. The association with the urinary tract was stronger for C. koseri BSI than for C. freundii complex BSI, which was more often polymicrobial and associated with abdominal surgery. Conclusion Citrobacter BSI was primarily found in elderly patients, either hospitalized or in close contact with healthcare in other ways. C. koseri BSI was to a greater extent associated with urinary tract focus compared to patients with BSI due to C. freundii complex, which was associated with abdominal source of infection and polymicrobial BSI.